Dealing With High Fertilizer Costs in Forage Production Systems - Maria L. Silveira; Joao M. Vendramini; Patrick J. Hogue; James F. Selph (EDIS)
SL-259, a 4-page fact sheet by M. L. Silveira, J. M. Vendramini, P. J. Hogue, and J. F. Selph, addresses important issues relative to fertilizer efficiency and suggests alternatives for reducing fertilizer use and reducing production costs for forage production. Published by the UF Department of Soil and Water Science, June 2008.